An analysis of public trust and confidence shown towards the Royal Malaysian Police in the social media / Nur Atiqah Sia Abdullah and Suziana Zamli - Sia Abdullah, Nur Atiqah; Zamli, Suziana (CMIWS and UiTM Press, 2014)
Public confidence is a concept that underpins the entire system of policing. The police force is constantly at risk of losing public confidence, due to a range of factors including falling levels of police visibility. Recent studies indicate increased interest in sentiment analysis research, especially in social media. Sentiment analysis research is a useful tool for analysing the public's perception of police misconduct as expressed in social media. Therefore, this study will be an attempt to improve the methods used by police organisations to improve public confidence in the police.